2021
DOI: 10.1038/s41598-020-80445-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a commercially formulated glyphosate solutions at recommended concentrations on honeybee (Apis mellifera L.) behaviours

Abstract: Glyphosate, the active ingredient of the most widely used commercial herbicide formulation, is extensively used and produced in China. Previous studies have reported sublethal effects of glyphosate on honeybees. However, the effects of commercially formulated glyphosate (CFG) at the recommended concentration (RC) on the chronic toxicity of honeybees, especially on their behaviours, remain unknown. In this study, a series of behavioural experiments were conducted to investigate the effects of CFG on honeybees. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Measured environmental concentration of glyphosate range between 1.4-7.6 mg•L −1 [119]. Changes in behavior were observed also at recommended concentrations of commercially formulated glyphosate [120]. Median lethal concentration for Banvel ® 480 S was determined to be 2519 µg•L −1 ; compared to A. fischeri bacteria, the toxic effect was observed at very similar concentrations.…”
Section: Crustacea Bioassay Testmentioning
confidence: 91%
“…Measured environmental concentration of glyphosate range between 1.4-7.6 mg•L −1 [119]. Changes in behavior were observed also at recommended concentrations of commercially formulated glyphosate [120]. Median lethal concentration for Banvel ® 480 S was determined to be 2519 µg•L −1 ; compared to A. fischeri bacteria, the toxic effect was observed at very similar concentrations.…”
Section: Crustacea Bioassay Testmentioning
confidence: 91%
“…It is known that exposure to GLY can alter the circadian cycle of A. mellifera bees (Vázquez, Balbuena, et al, 2020), which have three stages of sleep, repeated several times, in periods ranging from 10 to 15 min in the case of foragers (Eban‐Rothschild & Bloch, 2008). When not getting enough sleep, workers tend to reduce their learning/memorization ability and vertical displacement ability, jeopardizing essential tasks for colony maintenance (Luo et al, 2021; Vázquez, Balbuena, et al, 2020). In addition, during foraging, bees can make decisions based on previously memorized information, so chronic exposure to GLY can negatively impact the coordination of foraging activities, in addition to impairing the ability to fly, so bees may not return to the hive (Abraham et al, 2018; Luo et al, 2021).…”
Section: Sublethal Effects Of Glyphosate On Beesmentioning
confidence: 99%
“…The toxicological reference values for glyphosate in this study were: 1) the acceptable daily intake (ADI) at 0.3 mg kg − 1 body weight day − 1 (Renwick, 2002); 2) the acute reference dose (ARfD) at 0.5 mgkg − 1 body weight day − 1 (EFSA, 2015a); 3) the legally permitted maximum concentration of pesticide residues in or on food products or animal feed (MRL) at 0.05 mg kg − 1 (EFSA, 2017); and 4) the Acceptable Operator Exposure Level (AOEL) at 0.1 mgkg − 1 (EFSA, 2015b; Luo et al, 2021;Renwick, 2002). Next, we evaluated the health risk posed by glyphosate residues in pollen to consumers.…”
Section: Risk To Human Healthmentioning
confidence: 99%
“…Bees are insects with the highest risk of exposure due to the multiple routes to which they can be exposed when collecting nectar and pollen from blooming plants, carrying any contaminants in those resources to the hive (Agrebi et al, 2019;Coupe et al, 2012;Krupke et al, 2012). The main exposure routes include glyphosate-treated crops, drift, and the wide use of this herbicide in urban areas for domestic and minor applications, such as weed control on railways, parks, and home gardens (Pasquale et (James, 2016), applications of the herbicide glyphosate have intensi ed, bringing with it a greater health risk to honey bees (Agrebi et al, 2019;Bohan et al, 2005;Foulk, 2009;Rubio et al, 2014), due to the accumulation of pesticide residues inside the hives with chronic consequences, (Boily et al, 2013;Crenna et al, 2020;Herbert et al, 2014;Weisbrod, 2020;Wu et al, 2012;Zawislak et al, 2019), even though it is considered not toxic for adult bees (Lewis et al, 2016); for example, young adult bees chronically exposed to GLY formulations showed impaired associative learning and reduced sucrose sensitivity (Gonalons and Farina, 2018;Herbert et al, 2014;Luo et al, 2021) and forager bees exposed to sublethal doses of such formulations showed poor navigation back home (Balbuena et al, 2015).…”
Section: Introductionmentioning
confidence: 99%